2022
DOI: 10.3390/membranes12030342
|View full text |Cite
|
Sign up to set email alerts
|

Development of Free-Standing Titanium Dioxide Hollow Nanofibers Photocatalyst with Enhanced Recyclability

Abstract: Titanium dioxide hollow nanofibers (THN) are excellent photocatalysts for the photodegradation of Bisphenol A (BPA) due to their extensive surface area and good optical properties. A template synthesis technique is typically employed to produce titanium dioxide hollow nanofibers. This process, however, involves a calcination procedure at high temperatures that yields powder-form photocatalysts that require post-recovery treatment before recycling. Meanwhile, the immobilization of photocatalysts on/into a membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Devastatingly, BPA has estrogen-like and anti-androgen effects causing damages to different tissues and organs, including reproductive system, immune system and neuroendocrine system (Michałowicz, 2014;Ma et al, 2019). To eradicate such a contaminant, Jafri et al proposed the use of free-standing TiO 2 hollow nanofibers to photocatalytically mineralise BPA (Jafri et al, 2022). The process entails the attack of electron-rich C3 in the phenyl group of the BPA by HO • from the excited photocatalyst (see Figure 10).…”
Section: Treatment Of Other Eops Using Tio 2 and Zno Nanofibersmentioning
confidence: 99%
“…Devastatingly, BPA has estrogen-like and anti-androgen effects causing damages to different tissues and organs, including reproductive system, immune system and neuroendocrine system (Michałowicz, 2014;Ma et al, 2019). To eradicate such a contaminant, Jafri et al proposed the use of free-standing TiO 2 hollow nanofibers to photocatalytically mineralise BPA (Jafri et al, 2022). The process entails the attack of electron-rich C3 in the phenyl group of the BPA by HO • from the excited photocatalyst (see Figure 10).…”
Section: Treatment Of Other Eops Using Tio 2 and Zno Nanofibersmentioning
confidence: 99%
“…The published research studies have demonstrated that the three-dimensional hierarchical architectures assembled from the one-or two-dimensional nanostructured building blocks are an interesting class of materials with an abundant variety of tunable physicochemical properties [16]. Hierarchical porous hollow microstructures composed of single-crystalline two-dimensional nanosheets can provide low material density, good surface permeability, high surface area and electron transport rate, as well as high lightharvesting efficiency for application areas of catalysis and photovoltaic devices [17,18]. In this structure system, the material with micrometer-sized diameters can act as light scattering centers to increase the light harvesting of the photoanodes and photocatalysts, which is one of the crucial factors of improving the photovoltaic conversion efficiency of DSSCs and photocatalytic activity [19].…”
Section: Introductionmentioning
confidence: 99%